The Influence of Financial Ratios on Share Prices (Case Studies on Property & Realestate Companies in the Construction and Building Sub-Sector Listed on the Indonesia Stock Exchange) - Herlina Dwiyanthi; Neneng Faridatul Husna; Wili Handayani (Future Science, 2020)
This study aims to determine the effect of financial ratios on stock prices in property real estate companies in the construction and building sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period. By using the ratio of profitability, liquidity, and solvency. The financial ratios studied are Current Ratio (CR), Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Operating Profit Margin (OPM), as independent variables and stock prices as the dependent variable. In this study, researchers used as many as 8 sample companies. The data used are quantitative data on the annual financial statements of companies listed on the Indonesian stock exchange (BEI). This study uses multiple linear regression analysis using the SPSS program.